2015
DOI: 10.1364/oe.23.015716
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel SPR biosensor based on PCF for multi-analyte sensing applications

Abstract: This paper presents a theoretical investigation of a novel holey fiber (Photonic Crystal Fiber (PCF)) multi-channel biosensor based on surface plasmon resonance (SPR). The large gold coated micro fluidic channels and elliptical air hole design of our proposed biosensor aided by a high refractive index over layer in two channels enables operation in two modes; multi analyte sensing and self-referencing mode. Loss spectra, dispersion and detection capability of our proposed biosensor for the two fundamental mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(47 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…It is clear that the y-polarized fundamental core mode and the SPP mode occurs high coupling at the wavelength of 602 nm. Since some energy of the fiber waveguide mode is transfer into the energy of the SPR mode, making the loss spectra of the fiber core mod appears a loss peak at the resonance wavelength [26,27]. The RI of the analyte has a significant influence on coupling between the y-polarized core mode and the SPP mode.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the y-polarized fundamental core mode and the SPP mode occurs high coupling at the wavelength of 602 nm. Since some energy of the fiber waveguide mode is transfer into the energy of the SPR mode, making the loss spectra of the fiber core mod appears a loss peak at the resonance wavelength [26,27]. The RI of the analyte has a significant influence on coupling between the y-polarized core mode and the SPP mode.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…To our best knowledge, the theoretical value of the wavelength sensitivity (21700 nm/RIU) is highest sensitivity reported in D-shaped fiber SPR senor 25,26]. Compared to these design strategies of by the introduction of a small hollow core into MOF [1,11], optimizing air holes arrayed in MOF cladding [4][5][6][7][8][9][10], and sensitization processing at the polished surface [27], making PCF with lower RI material is a more effective method for improving sensitivity in D-shaped fiber SPR sensor.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…In comparison to bi-functional biosensors, Zhang et al have reported only sensitivity of 1535 nm/RIU for Channel 1and 1550 nm/RIU for Channel 2 and 3 [24]. Moreover, Otupiri et al [25] have introduced a maximum sensitivity of 4600 nm/RIU and 2300 nm/RIU according to HEx 11 and HEy 11 modes, respectively. Furthermore, the reported biosensor has more sensitivity than 4240 nm/RIU reported in [12], [26].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The dependence of the SPW on the changes of analyte RI is the underlying principle used in FOPS detection [47]. There are three main critical parameters for evaluating FOPS performance.…”
Section: Fops Performance Evaluationmentioning
confidence: 99%